2011
DOI: 10.1007/s10943-011-9533-1
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Healthy Behavior from the Pulpit: Clergy Share Their Perspectives on Effective Health Communication in the African American Church

Abstract: African Americans continue to suffer disproportionately from health disparities when compared to other ethnicities (ACS 2010; CDC 2007). Research indicates that the church and the pastor in the African American community could be enlisted to increase effectiveness of health programs (Campbell et al. in Health Edu Behav 34(6):864–880, 2007; DeHaven et al. in Am J Public Health 94(6):1030–1036, 2004). The objective of this study was to investigate African American pastors’ perceptions about health promotion in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 22 publications
2
58
1
Order By: Relevance
“…These findings suggest that "healthier" faith leaders are associated with "healthier" FBO environments, although because of the crosssectional design of the study, causal inferences are not possible. In a study of African American clergy, Lumpkins and colleagues 48 noted that pastors' personal experiences with health influenced their interactions with their congregation on issues related to health and pastors believed that they had considerable influence on church members' health-related concerns. Although further investigation of this relationship is warranted, it certainly provides merit for interventions targeting clergy health with the ultimate "downstream" goal of influencing the broader population through FBOs.…”
Section: An Examination Of Clergy Healthmentioning
confidence: 99%
“…These findings suggest that "healthier" faith leaders are associated with "healthier" FBO environments, although because of the crosssectional design of the study, causal inferences are not possible. In a study of African American clergy, Lumpkins and colleagues 48 noted that pastors' personal experiences with health influenced their interactions with their congregation on issues related to health and pastors believed that they had considerable influence on church members' health-related concerns. Although further investigation of this relationship is warranted, it certainly provides merit for interventions targeting clergy health with the ultimate "downstream" goal of influencing the broader population through FBOs.…”
Section: An Examination Of Clergy Healthmentioning
confidence: 99%
“…Almost all participants recruited in the second phase of this study were highly supportive of church-based health screenings, which is consistent with other research (Frank and Grubbs 2008). Previous research has found that church pastors serve an important role in raising awareness about health screenings (Matthews et al 2006), and pastors report viewing themselves as health promoters (Lumpkins et al 2013) and provide health education and access to health screenings in their church (Rowland and Isaac-Savage 2014). More research is needed to understand how African-American churches can assist in promoting and offering routine seeking health screenings, especially in considering churches' reach and influence with these populations.…”
Section: Discussionmentioning
confidence: 99%
“…Second, in both rural White and African-American communities, religious institutions occupy center stage as one of the few empowering, sustainable, and self-directed entities. (Corbie-Smith et al 2003; Leonard 1999; Lumpkins 2013) For many small, poor, rural communities, churches have been the only existing and sustainable organizational infrastructure, thus positioning the church to play a central role in community life and information-sharing. (Campbell et al 2007; Plunkett and Leipert 2013; Thomas et al 1994) Similar to the key roles of many African-American pastors, Appalachian pastors (some of whom in our project are also African-American), take on numerous and multidimensional healing roles, including serving as counselors, health educators and advocates, and even agents of change against stigmatized behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…(Campbell et al 2007; Plunkett and Leipert 2013; Thomas et al 1994) Similar to the key roles of many African-American pastors, Appalachian pastors (some of whom in our project are also African-American), take on numerous and multidimensional healing roles, including serving as counselors, health educators and advocates, and even agents of change against stigmatized behaviors. (Leonard 1999; Levin 1986; Lumpkins 2013)…”
Section: Introductionmentioning
confidence: 99%